HUBUNGAN DAYA LEDAK OTOT LENGAN DENGAN HASIL SHOOTING PADA SISWA/I EKSTRAKURIKULER PETANQUE SMP AL-FURQOON KOTA LUBUKLINGGAU - Septa Alpa Rizhi; Drajat Friansah; Wawan Syafutra (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
ABSTRACT The purpose of this study was to determine the relationship between arm muscle explosive power and the results of shooting petanque in Al-Furqoon Junior High School students, Lubuklinggau City. This study uses a quantitative approach with the product moment correlation method. The population in this study were all petanque students of SMP Al-Furqoon. The sample in this study was 20 students.Data collection techniques are using tests and measurements. Data analysis technique using correlation coefficient.The results of this study indicate that there is a positive relationship between the explosive power of the arm muscles and the results of shooting petanque. This can be seen from the calculation of the product moment rxy is 0,609 and if confirmed by the interpretation table the correlation is in the range 0,60-0,79 belonging to the strong category. Ha accepted The conclusion of the researcher is that there is a relationship between arm muscle power and the results of pentanque shooting in Al-Furqoon Junior High School students, Lubuklinggau City. Researchers suggest to get the right shooting results, it is necessary to increase the explosive power of the arm muscles. Keywords: arm muscle explosive power, petanque, shooting